2014 the European Conference on Optical Communication (ECOC) 2014
DOI: 10.1109/ecoc.2014.6963903
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity 40 Gbit/s preamplified SOA-PIN/TIA receiver module for high speed PON

Abstract: We demonstrate a receiver module which associates a preamplified detector with a transimpedance amplifier for next generation PON network. The module achieved in NRZ a very high sensitivity of -23 dBm at 25 Gbit/s and -21 dBm at 40 Gbit/s.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Therefore, many researchers have provoked considerable efforts to improve the sensitivity performance of PDs. In 2012, Nada et al reported that an APD together with a commercially available transimpedance amplifier (TIA) realized −21.7 dBm sensitivity at a data rate of 25.8 Gb/s which was assembled in the ROSA [48] . However, commercial APD above 10 Gb/s is scarcely available, and because of the low ionization coefficients ratio of the avalanche material, it is leading Ref.…”
Section: Research Hotspots Of Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many researchers have provoked considerable efforts to improve the sensitivity performance of PDs. In 2012, Nada et al reported that an APD together with a commercially available transimpedance amplifier (TIA) realized −21.7 dBm sensitivity at a data rate of 25.8 Gb/s which was assembled in the ROSA [48] . However, commercial APD above 10 Gb/s is scarcely available, and because of the low ionization coefficients ratio of the avalanche material, it is leading Ref.…”
Section: Research Hotspots Of Photodetectorsmentioning
confidence: 99%
“…This photoreceiver operates with 3 dB bandwidth up to 110 GHz and a dark current of 1 nA at 1.55 mm wavelength [50] . From 2012 to 2015, an integrated SOA-PIN photonic circuit with a high responsivity of 88 A/W and a large −3 dB bandwidth of 50 GHz [51] , a receiver with an integrated SOA-PIN chip and a TIA with a broad bandwidth of 35 GHz and a very high sensitivity of −23 dBm at 25 Gb/s and −21 dBm at 40 Gb/s [52,53] is achieved in succession by the Caillaud group shown in Fig. 1.…”
Section: Research Hotspots Of Photodetectorsmentioning
confidence: 99%
“…For example, to improve the gain and saturation output power, Raring et al 12) used quantum well mixing 13) and more than four metal-organic chemical vapor deposition (MOCVD) steps to achieve high-and low-optical-confinement SOAs on the same chip. Moreover, in order to improve the coupling efficiency of the SOA and fiber waveguide, III-V lab [4][5][6][7][14][15][16][17][18] employed electron beam lithography and up to three growth steps. Consequently, an approach that requires fewer growth steps is a simpler process and allows for the independent design of the SOA and PD.…”
Section: Introductionmentioning
confidence: 99%